Evaluation of Some Local Sorghum Checks Resistant to Shoot Fly (Atherigona soccata Rondani) and Stem Borer (Chilo partellus Swinhoe) - Bhagwat, V R; Prasad, G Shyam; Kalaisekar, A; Subbarayudu, B; Hussain, T; Upadhyaya, S N; Daware, D G; Rote, R G; Rajaram, V (Annals of Arid Zone, 2016)
Experiments were conducted to evaluate sorghum checks for resistance to shoot fly and stem borer at the Directorate of Sorghum Research, Hyderabad, and AICSIP centers (Surat, Udaipur, Indore, Coimbatore and Parbhani) during kharif 2007, 2008 and 2009. Taking into consideration six parameters viz., glossiness, seedling vigor, shoot fly deadhearts, stem borer deadhearts, tunnelling and exit holes/stalk due to borer, hierarchical clustering was done by centroid method. Three entries viz., IS 2312, IS 18551 and IS 2205 (resistant checks) were resistant and seven entries viz., JJ1041, PVK 809, CO 28(S), CSV 15, SPV 1616 and CSV 17 were moderately resistant to shoot fly and stem borer indicating multiple resistance. Key words: Sorghum, key pests, host plant resistance, local checks